Smartphones’ impact on nursing performances: a cross-sectional multicenter study - Di Simone, Emanuele; Dionisi, Sara; Giannetta, Noemi; Panattoni, Nicolò; De Leo, Aurora; Di Mario, Sofia; Surace, Antonella; Urban, Jessica; Liquori, Gloria; Napoli, Christian; Montesano, Marzietta; Di Muzio, Marco; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. In recent years, the technology world has significantly shaped society. This study aims to survey the views of registered nurses with hospital working experience regarding the personal communication devices use impact in hospital units. The secondary outcome of this study was to identify differences in mobile device use based on demographic and organizational factors. Study design. Cross-sectional study by survey. Methods. The questionnaire comprises 22 items divided into four sections. Overall 778 questionnaires were included in the study, 329 questionnaires were collected on pen-and-paper, whereas 449 by an online survey. Results. Findings showed that smartphones have a different impact on performance, utilization and impact scale according to gender, age and educational attainment. Generally males using more frequently personal communication devices for non-work-related activities affected negatively their working performance by respect to females. Moreover, younger nurses report being more distracted by using smartphones for non-work-related activities than older nurses. At the same time, younger nurses believe that smartphones may lead to an improvement in patient care skills. Nurses with fewer years of service (1 month - 10 years) report being more distracted by non-work-related activities on their smartphones than nurses with more years of service (>20 years). Conclusions. Mobile phones are a potential source of distraction. The most exposed groups are younger nurses and those with less work experience, and both (younger age, less experience) can be considered potential distraction factors.